Is 6-thioguanine more appropriate than 6-mercaptopurine for children with acute lymphoblastic leukaemia? - Lennard, L. (Nature Publishing Group, 1993)
The cytotoxic activity of 6-mercaptopurine (6-MP) is affected by thiopurine methyltransferase (TPMT), a genetically regulated and variable intracellular enzyme. 6-Thioguanine (6-TG), a closely related thiopurine, is less affected by that enzyme and so it may be a more reliable drug-at least for patients with constitutionally high TPMT activity. We attempted to assess its suitability as an alternative by comparing the pharmacokinetics of both drugs in a small group of children with lymphoblastic leukaemia (ALL). Patients were included who were in their second or subsequent remission, who would otherwise have received 6-MP, and on whom pharmacokinetic data concerning 6-MP metabolism had been collected in a previous remission. Plasma 6-TG concentrations were assayed following an oral dose of 40 mg m-2, and the accumulation and fluctuation of intracellular (erythrocyte, RBC) 6-TG nucleotides (6-TGNs) were measured at regular intervals during daily oral therapy. Seven children were studied. Plasma 6-TG concentrations were low and cleared within 6 h of oral dosing. At 7 days, 6-TGN concentrations ranged from 959 to 2361 pmol 8 x 10(-8) RBCs, in all cases significantly higher (P = 0.002) than those produced by the same patients on 6-MP. After a total therapy time of 35 patient months, a modest rise of alanine aminotransferase was seen on one occasion, otherwise no toxicity apart from myelosuppression was encountered. In the context used, 6-TG appears well tolerated and produces higher concentrations of intracellular cytotoxic metabolites than 6-MP. For children constitutionally 'resistant' to the traditional drug, if not all, it may be a preferable alternative.